2022
DOI: 10.3390/jcm11123464
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Satisfaction Using a New Augmented Reality Simulation Software for Breast Augmentation: A Prospective Study

Abstract: Background: Breast augmentation is one of the most frequently performed plastic surgery procedures. Providing patients with realistic 3D simulations of breast augmentation outcomes is becoming increasingly common. Until recently, such programs were expensive and required significant equipment, training, and office space. New simple user-friendly programs have been developed, but to date there remains a paucity of objective evidence comparing these 3D simulations with post-operative outcomes. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…18 La Padula et al developed simulation software to assess patient satisfaction following breast augmentation using augmented reality. 19 Zhou et al, in a systematic review of patient loyalty, revealed eight determinants, including trust, satisfaction, quality, commitment, value, hospital brand image, organizational citizenship behavior, and customer complaints. 3 Health service providers focusing on patient loyalty achieve more economic or noneconomic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…18 La Padula et al developed simulation software to assess patient satisfaction following breast augmentation using augmented reality. 19 Zhou et al, in a systematic review of patient loyalty, revealed eight determinants, including trust, satisfaction, quality, commitment, value, hospital brand image, organizational citizenship behavior, and customer complaints. 3 Health service providers focusing on patient loyalty achieve more economic or noneconomic benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation technology has been linked to high patient satisfaction. 17 We can foresee a future in which AI will be able to predict the type of surgery and implant needed for each patient. Although the world of completely automated surgical procedures is currently unrealistic, the technology we describe in this work is one of the necessary milestones that will one day bring us there.…”
mentioning
confidence: 99%